A historical controlled study of domestic trastuzumab and pertuzumab in combination with docetaxel for the neoadjuvant treatment of early HER2-positive breast cancer - Xu, Dongdong; Wu, Jiang; Yu, Jing; Yang, Yuqing; Wen, Xinxin; Yang, Jixin; Wei, Hongliang; Xu, Xiaolong; Li, Yike; Yang, Liu; Wang, Lei; Wang, Yijia; et al. (Frontiers in Oncology, 2024)
HER2-positive molecular breast cancer subtypes are characterized by high aggressiveness and 40 malignancy, and their metastasis and mortality rates are among the highest of all types of breast 41 cancer. The use of anti-HER2-targeted agents in neoadjuvant therapy has significantly improved the 42 prognosis of patients with HER2-positive breast cancer. In this study, we investigated the efficacy 43 and safety of a neoadjuvant Chinese THP regimen (docetaxel, trastuzumab biosimilar TQB211 plus 44 the pertuzumab biosimilar TQB2440 or pertuzumab) for ER/PR-negative and HER2-positive breast 45 cancer in China. All enrolled patients received the THP regimen (T: docetaxel 75 mg/m 2 per cycle; 46 H: trastuzumab biosimilar TQB211 8 mg/kg in the first cycle and 6 mg/kg maintenance dose in 47 cycles 2 to 4; P: pertuzumab biosimilar TQB2440 or pertuzumab 840 mg in the first cycle, 48 maintenance dose 420 mg in cycles 2 to 4) every 3 weeks for 4 cycles. The biosimilar TQB2440 49 pertuzumab and pertuzumab were randomly assigned to patients. Docetaxel, TQB211, and TQB2440 50 were all developed by Chiatai Tianqing. The primary endpoint was the pathological complete 51 response (pCR) in the breast, and the secondary endpoint was cardiac safety. Of the 28 eligible 52 patients, 19 (67.9%) achieved tpCR. The tpCR rate was higher than in the NeoSphere trial 53 (pCR63.2%) and the PEONY study (tpCR52.5%). The adverse events that occurred most frequently 54 were leukopenia and neutropenia, with incidence rates of 82.1% and 75.0%, respectively. Of these, 55 grade 3 leukopenia and neutropenia occupied 46.4% and 35.7%. Other grade 3 or higher adverse 56 events were bone marrow suppression (7.1%), lymphopenia (3.6%), and anemia (3.6%). There were 57 no events of heart failure in patients and no patient died during the neoadjuvant phase. Domestic 58 dual-target HP has a more satisfactory efficacy and safety in the neoadjuvant phase of treatment. 59 Clinical trial registration: CTR20201685 60